Intensidades vibracionais fundamentais de moléculas em estados eletronicamente excitados: SAC-CI e QTAIM/CCFDF - Martins, Gabriel Rodrigues (2017)
The Charge–Charge Flux–Dipole Flux (CCFDF) model using QTAIM parameters at the SAC-CI/cc-pVTZ calculation level was used to estimate XO2 (X = O, S, Se, Te) and H2X (X = O, S, Se, Te) fundamental vibrational intensities for ground and 15 low-lying electronic excited states. Charge flux, dipole flux, and its interactions were the most important contributions to the Q3 (for XO2) and Q2 (for H2X) modes of infrared intensities. Electronic Location Functions (ELFs) for H2X emphasize changes between dissynaptic and central atom monosynaptic valence basins when changing from ground to electronic excited states. XO2 ELFs, on the other hand, present electron migration to monosynaptic valence basins for both central and terminal atoms. Atomic polar tensor elements after geometry reorientation show that the largest variations in the CCFDF contributions are related to the charge flux. The results from the present work/Thesis indicate that QTAIM/CCFDF approach can be employed to interpret infrared intensities not only for ground, but also for electronic excited states.